Clostridium difficile in England: can we stop washing our hands? - Authors' reply. - Eyre, D; Dingle, K; Didelot, X; Quan, T; Peto, T; Wilcox, M; Walker, A; Crook, D (Lancet, 2017)
In their letter, Esther van Kleef and colleagues describe a mathematical model showing that hospital infection control interventions can preferentially reduce hospital-adapted strains over community-adapted strains within and outside hospitals, questioning our conclusion that restrictions in fluoroquinolone use were responsible for most of the decline in Clostridium difficile infection.1 “All models are wrong, but some are useful” (George E P Box). The key is not whether a model can reproduce findings from an empirical study, but whether the assumptions underpinning it are sufficiently plausible. Unfortunately, several features are implausible in van Kleef and colleagues' model, which seems more appropriate for meticillin-resistant Staphylococcus aureus (MRSA).